2018
DOI: 10.1002/gps.4928
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA m.13514G>A heteroplasmy is associated with depressive symptoms in the elderly

Abstract: Increased mtDNA heteroplasmy at m.13514A>G is associated with depressive symptoms in older men. Heteroplasmy may represent a novel biological risk factor for depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…Indeed, in MDD patients, a higher level of mtDNA oxidative damage was observed in leukocytes [ 138 ]. Other mtDNA impairments (e.g., mtDNA deletions and mtDNA mutations) were commonly found in depression [ 139 , 140 , 141 ]. ROS could also induce lipid membrane oxidation that could alter the permeability of both mitochondrial membranes [ 134 , 136 , 142 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in MDD patients, a higher level of mtDNA oxidative damage was observed in leukocytes [ 138 ]. Other mtDNA impairments (e.g., mtDNA deletions and mtDNA mutations) were commonly found in depression [ 139 , 140 , 141 ]. ROS could also induce lipid membrane oxidation that could alter the permeability of both mitochondrial membranes [ 134 , 136 , 142 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial diseases, resulting from mutations in either the mitochondrial or nuclear genomes, affect more than 10 in 100,000 individuals [8]. Psychiatric symptoms frequently correlate with mitochondrial dysfunction [9], as evidenced by a study that found a significant association between heteroplasmy in mtDNA m.13514G>A and depressive symptoms in the elderly [10]. Elevated mtDNA levels have also been associated with heightened anxiety [11].…”
Section: Introductionmentioning
confidence: 99%